Kajian Sertifikasi Halal Gratis (Sehati) Dengan Skema Self Declare Pada UMKM Dapur Mimi - Jumiono, Aji; Fitri, Zusi Eka; Mardiah, Mardiah (Jurnal Ilmiah Pangan Halal, 2023)
Self-declaration or a statement by a business actor is a statement by a business actor that guarantees that an individual or the organization has stated the requirements based on the policy related to the items identified and explained who is responsible for complying with the policy. Mimi Kitchen UMKM is one of the business actors engaged in the bakery product sector that has been selling in the Tanjung Unggat sub-district and does not yet have a halal certificate for his business. Free halal certification aims to obtain halal certification free of charge or free of charge for business actors who meet the requirements by means of a self-declared business actor's statement which is verified and validated by the halal product process assistant (PPH). This internship report activity aims to provide information about free halal certification (SEHATI), assist with digitalization and registration of SIHALAL for Mimi Kitchen MSMEs in obtaining halal certificates, and find out the problems of the free halal certification program (SEHATI) through self-declaring. This activity was carried out at Mimi's Kitchen UMKM on Jalan Sultan Machmud, Gang Kayu Ara No. 1 RT/RW 02/05, Tanjung Unggat Village, Bukit Bestari District, Tanjungpinang City, Riau Islands Province in April - May 2023. From the results of this activity, a halal certificate was obtained for the Mimi Kitchen MSME business with ID number 21110002632250523 which was issued on May 19, 2023.